Cattle owners' perceptions of African bovine trypanosomiasis and its control in Busia and Kwale Districts of Kenya - Machila, N.; Wanyangu, S.W.; McDermott, John J.; Welburn, S.C.; Maudlin, I.; Eisler, M.C. (Elsevier, 2003)
A study using a structured questionnaire was conducted in Busia District, Western Kenya and Kwale District, Coastal Kenya to obtain qualitative and quantitative information from 256 cattle owners about their production systems, their perceptions of the diseases encountered in their cattle, the drugs used, and other measures adopted to control trypanosomiasis in cattle. The predominant production system was mixed crop-livestock with farmers owning 2-11 local cattle on holdings between 2 and 5 ha. Approximately 15% of disease episodes in cattle were perceived to be trypanosomiasis, although the farmers' ability to make diagnoses was limited in that over half of the diagnoses were inconsistent with the clinical signs described. Drugs were generally obtained from agro-veterinary shops, and the farmers themselves administered slightly more than half of these. One third of drug treatments given to sick cattle were trypanocides, but over half of these trypanocidal treatments were given to cattle believed to have diseases other than trypanosomiasis.